Electrical load forecasting in the Vientiane area : an application of a simulation model - Bouttavong Boungnong; Shrestha, Ram M.; Lefevre, Thierry; Malik, A.S.; Sida-HRD (Mekong) (Bangkok : Asian Institute of Technology, 1996)
This study deals with analysis of load pattern of different customer categories and long term electricity demand forecasting in Vientiane Area. The survey and hourly load calculations were used to analyze load pattern of different customers categories, in order to derive the load curves of different sectors. From these load curves, load modulation coefficients for each sector in economy are obtained. Which is used as input to forecast long term peak load using Model for Analysis of Energy Demand (MAED) model. The Growth Rate and Electricity Intensity models were used to forecast electricity demand both in the total and some economic sectors. It was not possible to identify or use other prospective models because of unavailability of statistical data, country's situation etc. The result of the analysis shows that the electricity demand would be increasing at 9.3% using Growth Rate model and 9.34% using Intensity model, which is very closed to Ed i forecast for the period 1995 to 2010. Similarly peak load is forecasted to increase at 9.6% in Low Scenario and 12% in High Scenario.
Thesis (M.Eng.) - Asian Institute of Technology, 1996
A thesis submitted in partial fulfillment for the requirements for the degree of Master of Engineering.
Keywords: Electric power consumption -- Laos -- Vientiane -- Forecasting